Liquid–Liquid Phase Separation of the Green Mussel Adhesive Protein Pvfp‐5 is Regulated by the Post‐Translated Dopa Amino Acid. Issue 25 (26th August 2021) - Deepankumar, Kanagavel; Guo, Qi; Mohanram, Harini; Lim, Jessica; Mu, Yuguang; Pervushin, Konstantin; Yu, Jing; Miserez, Ali
Abstract: The underwater adhesive prowess of aquatic mussels has been largely attributed to the abundant post‐translationally modified amino acid l ‐3, 4‐dihydroxyphenylalanine (Dopa) in mussel foot proteins (MFPs) that make up their adhesive threads. More recently, it has been suggested that during thread fabrication, MFPs form intermediate fluidic phases such as liquid crystals or coacervates regulated by a liquid–liquid phase separation (LLPS) process. Here, it is shown that Dopa plays another central role during mussel fiber formation, by enabling LLPS of Pvfp‐5β, a main MFP of the green mussel Perna viridis . Using residue‐specific substitution of Tyrosine (Tyr) for Dopa during recombinant expression, Dopa‐substituted Pvfp‐5β is shown to exhibit LLPS under seawater‐like conditions, whereas the Tyr‐only version forms insoluble aggregates. Combining quantum chemistry calculations and solution NMR, a transient H‐bonding network requiring the two hydroxyl groups of Dopa is found to be critical to enable LLPS in Dopa‐mutated Pvfp‐5β. Overall, the study suggests that Dopa plays an important role in regulating LLPS of MFPs, which may be critical to concentrate the adhesive proteins at the plaque/substrate interface and therefore produce a more robust adhesive. The findings also provide molecular‐level lessons to guide biomanufacturing of protein‐based materials such as bioadhesives and load‐bearing fibers. Abstract : The underwater adhesive prowess of mussels is well‐known to be linked to the post‐translated amino acid l ‐3, 4‐dihydroxyphenylalanine (Dopa) present in high abundance in mussel adhesive proteins. Dopa is shown to play another important role in green mussel adhesive threads: it regulates liquid–liquid phase separation of the adhesive protein Pvfp‐5, enabling biofabrication of the adhesive thread under an immersed environment.